3D-augmentation of 2D ultrasound for appendicitis diagnosis: A cross-sectional pilot study - Rebecca G. Theophanous; Elias Jaffa; Matthew R. Morgan; Carl D. Herickhoff; Erica Peethumnongsin; Joao Ricardo Nickenig Vissoci; Joshua S. Broder (JEM Reports)
Background: Two-dimensional ultrasound (2DUS) is first-line imaging for pediatric appendicitis but is often nondiagnostic. Computed tomography (CT) is expensive with ionizing radiation. Three-dimensional ultrasound (3DUS) can capture multiplanar images using volume acquisition without radiation exposure. Objective: We hypothesized that bedside-performed 3DUS would be feasible, with rapid image acquisition times, and good image quality comparable to 2DUS and CT. Methods: We performed a cross-sectional pilot study on emergency department patients being evaluated for appendicitis. An emergency physician captured 3DUS images using a Sonosite M-Turbo machine equipped with an inertial measurement unit and customized software. Our primary outcome was 3DUS acquisition times compared to 2DUS and CT. Secondary outcomes were 3DUS image quality, with visual demonstrations of appendicitis findings compared to clinical imaging. Results: 20 subjects underwent an experimental 3DUS between October 2015 and March 2017. Mean age was 11.6 years (4.6–30.4 years). Five patients (25 %) had clinical appendicitis (2 by 2DUS and 3 by CT). Mean 3DUS acquisition and reconstruction times were 10.3 and 14.5 s, compared to 2DUS (41 min) and CT (22 min). Mean 3DUS pixels were 320.5 PPI depth, 388 PPI width, mean total frame number 344, and field of view 78.8°. Finally, we demonstrated two appendicitis complications on 3DUS: abscess and a dilated noncompressible appendix with appendicoliths. Conclusion: Our study suggests 3DUS is fast with good image quality. We presented 3DUS images of acute appendicitis comparable to 2DUS and CT as visual demonstrations of feasibility. Future studies with larger cohorts are needed to assess diagnostic accuracy.